Discursos e imagens da cidade: o processo de requalificação urbana de Campina Grande-PB (1970-2000) - Carvalho, Maria Jackeline Feitosa (2012)
This thesis seeks to understand the process of urban requalification which occurred in Campina Grande in the 1970 s, 1980 s, 1990 s and 2000 s, and it looks at the images and speeches interpreted by us, from the reading of official documents and the newspapers Diário da Borborema (DB) and Jornal da Paraíba (JP), as synthesis images which articulate the hegemonic speeches which open, in this context, the contemporary, urban, competitive, modern Campina and tech city. We are analyzing the institucional design of the town, from the public interventions which aim to modernize, to award new qualities and favour Campina, and finally the against uses of the town. By transforming the urban structure, and consequently, the social status in the town, the requalification imposes a clear hygienic process and inequalities in controversial landscapes, identified in this work as attempts of regeneration of the physical and social characteristics of the town. By pointing certain spaces out, through the speech which appoint the characteristics and singularities of Campina, the requalification activates a space process of disciplinary actions reaching the street vendors and the urban poor because of the attempts of their elimination of the central area of the town. Through this discussion, we are thinking about the street vendors and poor itineraries as ways for which the constituted order by the requalification is altered, through practices and manners which these users reappropriate the public space of Campina the streets, the pedestrian streets, the suburbs with a clear tension between the desired Campina and the accomplished town. To sum up, the images and speeches interpret Campina in what it means as urban experience, process which demarcates the elements of the competitive differentiation of the town, shows the space and social transformations occurred, in the analyzed period, and defines the ‗grammar which expresses the social landscape of the town nowadays.